368 Serial vs. single cardiovascular screening of adolescent athletes. (8th December 2021) - Sarto, Patrizio; Zorzi, Alessandro; Merlo, Laura; Vessella, Teresina; Pegoraro, Cinzia; Patti, Alessandro; Crosato, Martino; Thiene, Gaetano; Drezner, Jonathan; Basso, Cristina; Corrado, Domenico
Abstract: The primary objective of preparticipation cardiovascular evaluation (PPCE) in young athletes is to detect asymptomatic individuals with cardiovascular disease (CVD) at risk of sudden cardiac death (SCD). The study population included a consecutive series of competitive athletes age 12–18 years who underwent PPCE, which according to Italian law is mandatory and based on yearly evaluations, at the Center for Sports Medicine of Treviso (Veneto region of Italy), from 2009 to 2019. The screening protocol included personal and family history questionnaire, physical examination, resting 12-lead ECG, and limited stress testing for evaluation of exertional ventricular arrhythmias. 2, 3 This latter test was performed using a bicycle with constant-load increases (i.e. 2 W/kg in female participants and 3 W/kg in male participants) for 3 min for at least 85% or more of maximal heart rate was achieved, plus 3 min of postexercise monitoring. 3 Athletes with a positive medical history and abnormal physical examination, ECG, or stress test underwent further investigations. The diagnostic yield of the initial screening session was compared with that of repeat PPCEs. Athletes with a definitive diagnosis of CVD at risk of SCD were considered ineligible for competitive sports, although they received a tailored programme for leisure physical activity and were enrolled in a yearly follow-up programme. Outcome data of screened athletes, either eligible or ineligible to play competitive sports, were obtained from office visits, hospital records, or interrogation of the Registry of Juvenile SCD of the Veneto region. The study population included 15 127 consecutive athletes (64% male, 96% White) who underwent a total of 53 396 annual PPCEs (mean 3.7 per athlete) over the 11-year study period. The median age at first screening was 13 years [interquartile range (IQR): 12–14]. Sixty-three athletes (65% male) were diagnosed with a CVD at risk of SCD such as congenital heart disease ( n = 17), ion channel disease ( n = 11), inherited cardiomyopathy ( n = 13), isolated nonischaemic left ventricular scar (NLVS) with ventricular arrhythmias ( n = 18), or other ( n = 4); 266 athletes had cardiac conditions not associated with SCD. Seventeen of the 63 athletes (27%) with atrisk CVD had a positive family history, symptoms, or abnormal physical examination, 38 (60%) had ECG abnormalities, and 32 (51%) developed arrhythmias on limited exercise testing. CVDs more frequently identified on repeat evaluation included inherited cardiomyopathies [7/11 (64%)], NLVS with ventricular arrhythmias [15/18 (83%)], and long QT syndrome [7/11 (64%)]. During a mean follow-up of 6.7 ± 3.5 years, 1 athlete with a negative PPCE experienced an episode of aborted SCD attributable to ventricular fibrillation that remained unexplained after a comprehensive diagnostic workup (event rate, 0.98/100 000 athletes per year). These results show that annual cardiovascular screening of adolescent athletes increased by three times the diagnostic yield of CVD at risk of SCD compared with a once-only (initial) evaluation. Inherited cardiomyopathies and isolated NLVS with ventricular arrhythmias were the CVDs more frequently identified on repeat evaluation.